2014
DOI: 10.1186/1940-0640-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Review of the assessment and management of neonatal abstinence syndrome

Abstract: Neonatal abstinence syndrome (NAS) secondary to in-utero opioid exposure is an increasing problem. Variability in assessment and treatment of NAS has been attributed to the lack of high-quality evidence to guide management of exposed neonates. This systematic review examines available evidence for NAS assessment tools, nonpharmacologic interventions, and pharmacologic management of opioid-exposed infants. There is limited data on the inter-observer reliability of NAS assessment tools due to lack of a standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 52 publications
(69 reference statements)
1
96
0
Order By: Relevance
“…Prior studies have suggested improved NAS and birth outcomes in neonates exposed to buprenorphine compared to methadone, including decreased NAS severity with shorter length of hospitalization, lower risk of NAS pharmacologic treatment, and higher gestational age at birth, birth weight, body length and head circumference [1517]. Because of the potential for uncontrolled confounding in this and many studies published to date [18] we did not assess any causal relationships between prenatal exposure and infant outcomes. Further, the dynamic nature of clinical care in this patient population, including changes in both maternal treatment and in NAS treatment, can introduce misclassification bias in any causal assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have suggested improved NAS and birth outcomes in neonates exposed to buprenorphine compared to methadone, including decreased NAS severity with shorter length of hospitalization, lower risk of NAS pharmacologic treatment, and higher gestational age at birth, birth weight, body length and head circumference [1517]. Because of the potential for uncontrolled confounding in this and many studies published to date [18] we did not assess any causal relationships between prenatal exposure and infant outcomes. Further, the dynamic nature of clinical care in this patient population, including changes in both maternal treatment and in NAS treatment, can introduce misclassification bias in any causal assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Recent national trends in adjunctive medications for NAS favor clonidine as an acceptable option over phenobarbital [24, 25]. There is also a trend towards more emphasis on breastfeeding, rooming-in, and other non-pharmacologic care interventions to best manage NAS [18, 26]. Lastly, though the Finnegan scale is the current gold standard for NAS assessments, newer scales are under development [26].…”
Section: Discussionmentioning
confidence: 99%
“…In a national survey of practice, O'Grady et al 7 reported use of different protocols and screening tools in neonatal units and some units had no protocol in place. Where screening tools are used to detect NWS, inter-rater reliability coefficients of scoring methods range from 0.77 to 0.98 and small sampled studies have shown both specificity and sensitivity close to 100% 7 32. Under-recording may occur if the mother is not identified during pregnancy and the neonate is discharged soon after delivery 33…”
Section: Discussionmentioning
confidence: 99%
“…In our exploration of the association of hospital policies with LOT and LOS, we find that standardizing the NAS-scoring process was associated with decreases in LOT of -2.1 days (95% CI, -3.6 to -0.6) and LOS of -3.1 days (95% CI, -4.9 to -1.4), after accounting for infant characteristics and other hospital policies. Several scoring systems for NAS have been shown to suffer from problems of interrater reliability, 20 making it an optimal target for improvement. Importantly, the interaction of standardizing scoring according to audit number was tested and was not statistically significant, suggesting that either our hospital sample was not large enough to detect a change or that this finding was associated mainly with hospitals that had a policy in place for the duration of the collaborative.…”
Section: Discussionmentioning
confidence: 99%